1998
DOI: 10.1002/(sici)1099-1573(19980201)12:1<18::aid-ptr180>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antiinflammatory medicinal plants used in traditional medicine against skin diseases

Abstract: The antiinflammatory activity of twelve medicinal plants used against skin disorders were tested in different experimental models of topical inflammation and one in vitro inhibitory test against phospholipase A 2 (PLA 2 ) from Naja naja venom. Forsythia suspensa was the most active species on the arachidonic acid (AA) topical test. This last species together with Astragalus membranaceus and Ranunculus sceleratus were the most active on the 12-O-tetradecanoylphorbol-13-acetate (TPA) acute ear oedema test. Scrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Astragalus species have been used traditionally to raise immune resistance, improve physical endurance and lower blood pressure [4]. Astragalus species have anti-inflammatory, analgesic, hypotensive, sedative, cardiotonic, hepatoprotective, antioxidative, antiviral and immunostimulant properties [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus species have been used traditionally to raise immune resistance, improve physical endurance and lower blood pressure [4]. Astragalus species have anti-inflammatory, analgesic, hypotensive, sedative, cardiotonic, hepatoprotective, antioxidative, antiviral and immunostimulant properties [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional clinical applications, Forsythiae Fructus is commonly used to treat boils, carbuncles, mumps, tonsillitis, urinary tract infections, allergic rashes, colds or flu-like symptoms (e.g. fever, chills, and headache), etc 1516…”
mentioning
confidence: 99%
“…Many morphological and physiochemical studies have been reported on commonly used plant parts of the Curcuma such as rhizome (Satyendra et al, 2013), leaves (Cuellar et al, 1998), stem (Dung et al, 1997), roots (Dung et al, 1996), inflorescence/ flowers and buds (Dung et al,1998) and Entire plant (Maikhuri and Gangwar, 1993). From all evidences, the leaf, flowers, fresh and dry rhizomes are important in obtaining different phytochemical effects as a medicine as well as for other uses.…”
Section: Studies On Genus Curcumamentioning
confidence: 99%
“…Roots attached to the rhizome often bear conical or ellipsoid tubers (Dung et al, 1997). Basal leaf blades are normally broad, lanceolate or oblong or rarely linear in shape (Cuellar et al, 1998). Flowers contain a single versatile anther and spiral bract with large compound spike inflorescence is a prominent characteristic when recognizing the genus Curcuma (Dung et al, 1998).…”
Section: Morphological Characteristics Of Genus Curcumamentioning
confidence: 99%